Pengembangan Potensi, Bakat, dan Minat Peserta Didik Melalui Kegiatan Ekstrakurikuler di Sekolah Dasar - Asti Widiastuti; Elsa Aulia Fadhilah; Hikmatul Ghina; Agus Mulyana (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
Potential, talents and interests certainly need to be developed and started as early as possible. Therefore, developing potential, talents and interests has been implemented since elementary school level. This article was created using qualitative methods which emphasize an in-depth understanding of the matter being studied. One of the private elementary schools, to be precise in one of the regions/regions of Bandung, has provided a platform for developing the potential, talents and interests of its students through extracurricular activities. The school has organized and facilitated approximately two mandatory extracurriculars and seven optional extracurriculars as an effort to develop students' potential, talents and interests in both academic and non-academic fields.